Solitary splenic metastasis in a case of treated cervical cancer: a case report - Shankar, Shetty Theertha; Panse, Mangesh; Goel, Arjun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Cervical cancer is the second most common cancer among women worldwide and metastasis to the spleen is a rare entity, with only few cases being reported. The present case of a 55-year-old patient diagnosed with a splenic lesion 3 years following completion of chemotherapy combined with radiotherapy for advanced cervical cancer. The patient underwent diagnostic laparoscopy with splenectomy. The histopathological studies confirmed the presence of a metastatic squamous cell carcinoma (in a known case of treated cervical cancer). At one-year follow-up after splenectomy, the patient was free of any recurrent disease. Owing to its rarity and scant data available, detailed workup should be done whenever a solitary lesion in the spleen is detected on follow-up since splenectomy is the apt management which is instrumental in preventing further complications and improves the survival rates.